EFFORTS TO IMPROVE LANGUAGE SKILLS THROUGH THE PICTURE BOOK STORYTELLING METHOD IN CHILDREN AGED 5-6 YEARS CHILDREN AT MARIA NAMORAMBE KINDERGARTEN : EFFORTS TO IMPROVE LANGUAGE SKILLS THROUGH THE PICTURE BOOK STORYTELLING METHOD IN CHILDREN AGED 5-6 YEARS CHILDREN AT MARIA NAMORAMBE KINDERGARTEN - Devi Tarigan; Juli Yanti Harahap (incrementapedia, 2023)
Early childhood education is the beginning in forming a child's character and attitudes. Early childhood knowledge and learning strategies are needed. This is needed to explore children's interest in language skills. Early childhood language skills can arise if there is external stimulation. One of them uses the storytelling method. This research discusses the low language skills of young children. The aim of this research is to improve the language skills of young children through the storytelling method. Children's language skills seen from conversations are quite clear, they are skilled at pronouncing and understanding words, they are able to follow the storyline, they enjoy poetry, humor word games and their vocabulary has developed to reach 1500 words. This type of research is classroom action research (PTK) using the picture book storytelling method for children aged 5-6 years at Mary's Children's Kindergarten Namorambe T.A 2022/2023. This research consists of two cycles, namely cycle I and cycle II. At each meeting the researcher conducts learning outcomes tests on children to determine the child's improvement. In the pre-cycle the average score for children was 38%, in the first cycle the average score was 64.32%. in cycle II the average was 89% and the percentage of children categorized as developing very well in learning each cycle also increased. Using the picture book storytelling method can improve the language skills of young children at Mary's Children's Kindergarten Namorambe T.A 2022/2023.